THE ROLE OF THE FOOD AND AGRICULTURE ORGANIZATION (FAO) IN EFFORT TO TACKLE FOOD INSECURITY IN CAMBODIA 2016-2018 - Darmayanti, Made Indah Desiana; Rainy Priadarsini, Ni Wayan; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
This study aims to describe the role of the international organization FAO in effort to tackle food insecurity in Cambodia in 2016-2018 in terms of the Monitoring Function and Development Function at local and national level by using descriptive qualitative method. The problem of food insecurity that has an impact on the high rates of malnutrition specifically childhood malnutrition is extremely widespread in Cambodia gain major concern from FAO. As a United Nations agency, FAO established a collaboration between FAO and the Royal Government of Cambodia through Country Programming Framework (CPF). FAO is striving to tackle food insecurity in Cambodia by establishing a framework that provides evaluation tools through Country Programming Framework (CPF), and implement the mechanisms international organizations can adopt to create enabling conditions at local level through various programs such as Farmers Business School (FBS), Project for Agricultural Development and Economic Empowerment (PADEE), and Participatory Guarantee Systems (PGS) ; and national level through Food and Nutrition Security Impact, Resilience, Sustainability and Transformation (FIRST) program . Therefore researcher used the framework of food security and the role of international organization in achieving food security to answer FAO’s role in effort to tackle food insecurity in Cambodia in 2016-2018 in terms of the Monitoring Function and Development Function at local and national level. Keywords : Cambodia, Food Security, The Role of International Organizations, Food and Agriculture Organization